Draft Annual Plan 1994-95 Government of Rajasthan - Planning Commission (Planning Commission, 1994)
Rajasthan State, In Its present form, Is a conglomeration of 19 princely States and 3 chiefships which varied in size, population, administrative efficiency and socioeconomic development. Administratively, Rajasthan Is divided into 30 districts, which are further sub-divided into 213 tehsils and 237 development blocks.
Planning Department, Government of Rajasthan